1981
DOI: 10.1073/pnas.78.2.1233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amphotericin B, nystatin, and other polyene antibiotics on chitin synthase.

Abstract: The effects of amphotericin B (AmB), nystatin, filipin, and pimaricin were tested on purified chitin synthase (EC 2.4.1.16) (chitosomes from yeast cells of Mucor rouxii). AmB and nystatin inhibited the enzyme at concentrations 210 #g/ml, filiin was weakly inhibitory, and pimaricin had no effect. The inhibition of chitin synthase by AmB appears to be noncompetitive, with a K; value of about 0.13 mM. The effect of nystatin was more complex and included a sharp stimulation of chitin synthase activity at "'50 jug/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 21 publications
4
4
0
Order By: Relevance
“…This notion is supported by previous results [22], which show the non-competitive inhibition of puri¢ed chitin synthetase by a high concentration of AmB.…”
Section: Chitinase Production In Relation With Yeast Cell Growthsupporting
confidence: 80%
“…This notion is supported by previous results [22], which show the non-competitive inhibition of puri¢ed chitin synthetase by a high concentration of AmB.…”
Section: Chitinase Production In Relation With Yeast Cell Growthsupporting
confidence: 80%
“…Secondly, during germ tube formation certain synthetic activities are concentrated at restricted regions of the cell (10 is possible that AmB causes cell death by localizing to these regions and preferentially inhibiting the formation of new cell wall. Rast and Bartnicki-Garcia demonstrated that AmB inhibits chitin synthase at concentrations around 1 pLg/ml (8). This formulation would not require an increase in total drug uptake and would be supported by the observation that germ tube lengthening is inhibited by AmB but that new second germ tubes can develop.…”
mentioning
confidence: 71%
“…Amphotericin B at concentrations in excess of the minimum growth inhibitory concentrations, inhibits chitin synthase in chitosomal preparations from filamentous fungi (Rast and Bartnicki-Gareis, 1981). This may result from the polyene affecting the lipid environment of the enzyme and hence its activity.…”
Section: The Biological Effects Of Amphotericin Bmentioning
confidence: 99%